Temperature effect on exchange coupling and magnetization reversal in antiferromagnetically coupled (Co/Pd) multilayers - Sbiaa, R. (2015)
Magnetization reversal of antiferromagnetically coupled (AFC) soft and hard (Co/Pd) multilayers was studied as a function of temperature. While the hard [Co(0.3 nm)/Pd(0.8 nm)]×10 was kept unchanged, the softness of the [Co(t)/Pd(0.8 nm)]×3 was controlled by varying the thickness t of the Co sublayer. Clear two-step hysteresis loops were observed for all the investigated multilayers with t ranging between 0.4 and 1 nm. The spin reorientation of the soft layer magnetization from in-plane direction to out-of-plane direction was investigated from 50 to 300 K. The antiferromagnetic field H AFC measured from the shift of the minor hysteresis loop reveals a good agreement to the quantum-well model. From the out-of-plane hysteresis loop of the uncoupled soft layer, its magnetization shows an in-plane orientation for t ≥ 0.6 nm. The strong H AFC helps to induce an out-of plane orientation of the soft layer with a linear decrease of its coercivity with temperature. These investigated structures show the possibility to reduce the unwanted stray field and improving the out-of-plane anisotropy even for relatively thicker soft layer.